Implementasi Kepemimpinan Dalam Meningkatkan Kinerja Guru Di Sekolah Menengah Atas - Stefani Intan Marukedu; Sara Dedo Ngara; Yohanis Malo; Laurens Ricardo Nani Boeloe; Yosep Bili Bora; Marvel Maramba Amah (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2024)
This research examines the implementation of leadership in improving teacher performance at Alfonsus Weetebula Catholic High School. The main focus of the research is to understand how the leadership style applied by school principals can influence teacher motivation, professionalism and work effectiveness. This research uses a quantitative method with a case study approach, where data is collected through in-depth interviews, observation and analysis of related documents. The research results show that transformational and participative leadership have a significant impact on improving teacher performance. School principals who are able to provide a clear vision, emotional support, as well as recognition and appreciation for teacher achievements, can create a more positive and productive work environment. In addition, training and continuous professional development were also found to be important factors in supporting improved teacher performance. This research concludes that the implementation of effective leadership in high schools is the main key in improving the quality of education through improving teacher performance.